Himalayan Neotectonics and Channel Evolution - Bhattacharya, Harendra Nath.; Bhattacharya, Soma.; Das, Balai Chandra; Islam, Aznarul (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book focuses on neotectonic movements and river channel evolution of the Indian subcontinent, with special reference to the Himalayan Neotectonics. Neotectonic movements have played an important role in channel evolution in tectonically active zones especially for the mountain chains, foredeeps and active deltas. The book addresses the issues of the channel evolution in neotectonically active domains of India. It aims at readers of India as well as abroad, interested in earth sciences, geomorphology, tectonics, physical geography and river forms and processes of India. .
Neotectonic Movements and Channel Evolution in the Indian Subcontinent: Issues, Challenges and Prospects -- Dramatic Neotectonic Changes in Indian Subcontinent during Quaternary -- Influence of tectonic uplift on varying steepness-concavity index and erosion rates in between major thrusts in Bhagirathi-Alaknanda catchments, NW Himalaya, India -- Spatial variability of topographic attributes and channel morphological characteristics in the Ladakh Trans-Himalayas and their tectonic and structural controls -- Geomorphic response of the Solani river basin to neotectonics: A study from the western Himalayan foothills, India.
Keywords: Earth sciences; Geodynamics; Geophysics; Geomorphology; Earth Sciences; Geodynamics; Geophysics; Geomorphology